RESEARCH ON THE APPLICATION OF ERGONOMICS IN ACTIVITIES RELATED TO ENGINEERING LOGISTICS: RESEARCH ON THE APPLICATION OF ERGONOMICS IN ACTIVITIES RELATED TO ENGINEERING LOGISTICS - Yankova-Yordanova, Yordanka; Doychinov, Yordan; Vachinska-Aleksandrova, Soniya; Yordanov, Nikolay (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The rapid advancement of modern science and technology demands that engineering professionals possess not only technical expertise but also the ability to effectively manage the human factor within logistics processes. This article explores the role of ergonomics as a strategic tool in engineering logistics for optimizing workflows, enhancing safety and efficiency, and fostering sustainable models in engineering education. The study examines the interconnection between the physical, cognitive, and organizational dimensions of ergonomics and their impact on logistics activities. It presents practical methods for integrating ergonomic principles into engineering systems through digital technologies such as virtual simulation, artificial intelligence, and the internet of things. Case studies from leading companies, including Siemens, Toyota, and DHL, illustrate the tangible benefits of ergonomic applications in logistics environments. The paper emphasizes the importance of incorporating ergonomics into strategic management and engineering curricula to build interdisciplinary competencies. Ultimately, the integration of ergonomic design with digital transformation offers a pathway toward intelligent, human-centered, and sustainable engineering logistics systems.